Wearable Electronics: Multifunctional Ultrastretchable Printed Soft Electronic Devices for Wearable Applications (Adv. Electron. Mater. 2/2020). (13th February 2020) - Tian, Bin; Liu, Qun; Luo, Chengsheng; Feng, Yu; Wu, Wei
Abstract : In article number 1900922, Wei Wu and co‐authors demonstrate printed soft multifunctional electronic devices that exhibit ultra‐stretchability and high conductivity. The orange‐red and blue halo effects in the cover image represent the excellent Joule heating performance and outstanding sensing performance of these multifunctional electronic devices. They are successfully applied to detect joint motion, thermochromism, and hyperthermia, showing great application potential in the field of next‐generation multifunctional and smart wearable electronics.